Relation Between Chromium Contaminant Profile and Mollusk Community Structure In Opak River: HUBUNGAN PROFIL CEMARAN KROMIUM DENGAN STRUKTUR KOMUNITAS MOLUSKA DI SUNGAI OPAK - Ma'dika, Geraldine Apriceline; Raharjo, Djoko; Kisworo, Kisworo (Universitas Jambi, 2021)
The used of chromium (Cr) in tannery industrial area in Banyakan Village, Piyungan has been proven to pollute river components and the mollusk community structure. From the results, chromium was found in water with a concentration range of 0.0004 - 0.975 mg/L with an average concentration of 0.053 mg/L. While in sediments with a range of 0,0004 - 2,730 mg/kg with a average concentration of 1,015 mg/kg. Chromium in mollusk was found with range of 0.0004 - 2.761 mg/kg with an average of 1.065 mg/kg. From the identification of the mollusk community, it was found 19 species and 2 classes of mollusks, which is Gastropods and Bivalvia. Sulcospira testudinaria became the highest chromium accumulation in all species (1,555 mg/kg). The results of the correlation test between the chromium concentration in water and sediment and chromium concentration in mollusks did not have a significant effect.